Load Balanced User Association Scheme in Planned Non-bias Small Cell Deployment - Siva Priya Thiagarajah; Mohamad Yusoff bin Alias; Wooi-Nee Tan (IJAIT (International Journal of Applied Information Technology), 2022)
The work presented in this paper focuses on developing a load-balanced user association scheme in a single Radio Access Technology (RAT) Heterogeneous Networks (HetNet). The optimization algorithm maximizes network capacity and optimal user association in a planned small cell deployment framework, considering Quality of Service (QoS) and network load balance. Planned deployment of small cells has many advantages, including controlled interference levels within the HetNet. The proposed Branch and Bound (BAB) based algorithms provide a more realistic interference scenario through the non-use of bias in the small cells. The proposed algorithm achieved higher load balancing than current schemes in literature and high spectral efficiency values.